Scheduling with time-of-use costs - Chen, Bo; Zhang, Xiandong (European journal of operational research, 2019)
•Detailed picture of computational tractability for the scheduling problems at hand.•Efficient algorithms for tractable problems.•A fully polynomial-time approximation scheme for an intractable problem. We address a class of problems of scheduling a set of independent jobs onto a single machine that charges each job for its processing under variable time-of-use tariffs. Our scheduling objective is to minimize the total cost of processing all the jobs subject to a minimum level of performance in one of the regular scheduling criteria. For each of the problems in the class, we establish its computational tractability. For those that are tractable we provide an efficient algorithm, while for those that are intractable we provide a pseudo-polynomial-time algorithm or a polynomial-time approximation scheme.